f ( 1 ) + f ( 2 ) + f ( 3 ) + … + f ( n ) = n 2 f ( n )
Consider a function f ( x ) satisfying the equation above for n ≥ 1 with f ( 1 ) = 2 0 0 5 .
Find the sum of digits of f ( 2 0 0 4 ) 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Yes telescoping product is the key here! This is one way to find the answer without explicitly determining the formula for f ( n ) . Well done.
Did it the same way.
Induction:
f ( 1 ) = 1 a , f ( 2 ) = 3 a , f ( 3 ) = 6 a , f ( 4 ) = 1 0 a , f ( 5 ) = 1 5 a . . . . . . . . d i f f o f D r = 2 f ( 1 ) = 1 a , f ( 2 ) = 3 a , d i f f o f D r = 3 f ( 2 ) = 3 a , f ( 3 ) = 6 a , d i f f o f D r = 4 f ( 3 ) = 6 a , f ( 4 ) = 1 0 a , d i f f o f D r = 5 f ( 4 ) = 1 0 a , f ( 5 ) = 1 5 a . . . . .
Clearly Denominator (Dr) terms have 2nd order difference constant , So it must satisfy 2nd order polynomial , Hence
∴ D n = A n 2 + B n + c ∵ D 1 = 1 , D 2 = 3 , D 3 = 5 ⇒ D n = n ( n + 1 ) / 2 f ( n ) = D n 2 a = n ( n + 1 ) 2 f ( 1 )
Now re-checking this by induction . f o r n = 1 : R H S = 1 . 2 2 f ( 1 ) = f ( 1 ) = L H S
Let f(K) is true for some K , then we have to prof f(K+1) is also true , to complete our target .
f o r n = K : f ( k ) = k ( k + 1 ) 2 f ( 1 ) . . . . ( A ) f o r n = K + 1 : R H S = ( k + 1 ) ( K + 2 ) 2 f ( 1 ) = f ( K + 1 ) = L H S H e n c e f ( n ) = n ( n + 1 ) 2 f ( 1 ) ∀ n ∈ N
With f ( 1 ) = 2 0 0 5 , f ( 2 0 0 4 ) = 2 0 0 4 × 2 0 0 5 2 × 2 0 0 5 = 1 0 0 2 1 . Answer is simply 1 + 0 + 0 + 2 = 3 .
You can simplify your first half of your work by observing that the denominators of f ( n ) are triangular numbers, so you can move to induction step immediately. Good work nonetheless.
@Nishu sharma , we really liked your comment, and have converted it into a solution. If you subscribe to this solution, you will receive notifications about future comments.
Problem Loading...
Note Loading...
Set Loading...
First thing we get that, n = 1 ∑ n − 1 f ( n ) = f ( n ) ( n 2 − 1 ) . . . . . . . . . . . . . . ( 1 ) n = 1 ∑ n − 2 f ( n ) = f ( n − 1 ) ( ( n − 1 ) 2 − 1 ) . . . . . . . . . . . . . . ( 2 ) ⟹ ( 1 ) − ( 2 ) = f ( n − 1 ) = f ( n ) ( n 2 − 1 ) − f ( n − 1 ) ( n 2 − 2 n ) ⟹ f ( n − 1 ) ( 1 + n 2 − 2 n ) = f ( n ) ( n 2 − 1 ) ⟹ f ( n − 1 ) ( ( n − 1 ) 2 ) = f ( n ) ( n − 1 ) ( n + 1 ) ⟹ f ( n − 1 ) ( n − 1 ) = f ( n ) ( n + 1 ) ⟹ f ( n − 1 ) f ( n ) = n + 1 n − 1 .Now,you can put values and multiply and all the terms except for two will cancel.: f ( 1 ) f ( 2 ) × f ( 2 ) f ( 3 ) × f ( 3 ) f ( 4 ) . . . × f ( 2 0 0 2 ) f ( 2 0 0 3 ) × f ( 2 0 0 3 ) f ( 2 0 0 4 ) = 2 2 0 0 5 ! 1 2 0 0 3 ! = 2 2 0 0 5 × 2 0 0 4 1 1 = 2 0 0 5 × 1 0 0 2 1 .And the L.H.S = f ( 1 ) f ( 2 0 0 4 ) .Hence, f ( 1 ) f ( 2 0 0 4 ) = 2 0 0 5 × 1 0 0 2 1 ⟹ 2 0 0 5 f ( 2 0 0 4 ) = 2 0 0 5 × 1 0 0 2 1 ⟹ f ( 2 0 0 4 ) 1 = 1 0 0 2 . Hence answer is 3 .